Sustainable production of bioethanol from renewable brown algae biomass. (September 2016) - Lee, Ok Kyung; Lee, Eun Yeol
Abstract: Brown algae have been considered as renewable biomass for bioethanol production because of high growth rate and sugar level. Saccharification of brown algae biomass is relatively easy due to the absence of lignin. Among the major sugar components of brown algae, alginate cannot be directly used because industrial microorganisms are not able to metabolize alginate. This problem has been overcome by the development of metabolically engineered microbes to efficiently utilize alginate. This review analyzes and evaluates recent research activities related to bioethanol production from brown algae. This review mainly deals with the recent development and potential of a metabolically engineered microbial cell factory and bioethanol production from brown algae biomass including alginate as the main carbohydrate. Future researches for cost-effective bioethanol production from brown algae are discussed. Highlights: This review deals with bioethanol production from brown algae biomass. Benefits of brown algae as biomass for bioethanol production were evaluated. Bioethanol production using metabolically engineered microorganisms was evaluated. Future researches for cost-effective bioethanol production from brown algae are discussed.